Development of Assemblr-Edu Based Learning Media with RADEC Learning Model on Implementation of P5 in Elementary School - Firdausya, Berlin Tirta Wening; Fatayan, Arum (Jurnal Paedagogy, 2024)
This research aims to develop Assemblr Edu learning media with the RADEC learning model for implementing the Pancasila Student Profile Strengthening Project (P5) in Elementary Schools. This research used the R&D (Research and Development) method with the 4D model. The research subjects consisted of material validators, media validators and 58 students. The data collection instrument used in this research was a questionnaire which was then analyzed descriptively qualitative and quantitative. The results of this study indicated that Assemblr Edu learning media based on the results of material validation obtained 97% with a very feasible category, and the results of media validation obtained 92% with a very feasible category. Educators could apply the results of the Assemblr Edu learning media development in implementing P5 with the RADEC learning model in elementary schools. This research makes a significant contribution to the education field, especially in utilizing Assemblr Edu technology and the RADEC learning model in elementary schools. In practice, it can enrich the literature on technology-based learning and educational innovation to improve the quality of high-quality learning.